Refractive error after combined phaco-vitrectomy: A multicentric study. Issue 2 (March 2023) - Kilian, Raphael; Crincoli, Emanuele; Rizzo, Clara; Ripa, Matteo; Faraldi, Francesco; Lavia, Carlo; Tartaro, Ruggero; Ceruti, Piero; Casini, Giamberto; Rizzo, Stanislao; Savastano, Alfonso
Purpose: To study the post-operative refractive error (RE) of patients undergoing combined phaco-vitrectomy and to find out which intraocular lens (IOL)-power formula had the best refractive outcomes. Methods: In this retrospective multicentric study we compared the preoperative expected target with the postoperative RE of patients undergoing combined phaco-vitrectomy due to vitreomacular traction, macular pucker, full thickness macular hole or lamellar macular hole. A multinomial logistic regression was performed to compare the postoperative REs and the differences between expected and postoperative REs among the SRK-T, Olsen's and Holladay-2 formulas. The correlation between the difference in REs and IOL-power was also studied. Results: Sixty-seven eyes with a mean axial length of 23.73 ± 1.21 mm were included. Forty-two (63%), 14 (21%) and 11 (16%) eyes were implanted with an IOL that was calculated respectively with SRK-T, Olsen's and the Holladay-2 formula. The mean preoperative expected- and post-operative REs were −0.16 ± 0.12D and −0.48 ± 0.17, respectively ( p = 0.045). SRK-T and Holladay-2 formulas led to a significant myopic shift whereas Olsen's caused a significant hyperopic error, independently from the IOL power. Conclusion: Independently from the IOL power, none of the analyzed formulas is precise at calculating the post-operative RE.